EFL Students’ Interest and Their Reasons towards Recreational Reading Activity - Maha Putri, Kadek Indah; Masakawati, Ni Putu Era; Tantra, Dewa Komang (Lingua Scientia, 2021)
Students’ interest in reading has been studied by many researchers.  However, there is little attention given to examining the interest of EFL students on recreational reading activity. Additionally, few studies have documented why EFL students have certain interests on the recreational reading activity. To fill this gap, why students have certain interest in recreational reading and the reasons why students have. This paper aims at describing the EFL students' interest of choosing recreational reading and their reasons for choosing the activity. To achieve this aim, the research used qualitative case study. By administering purposive sampling technique, five EFL students at the sixth grade were selected as the research participants. Data were collected from interview. The collected data were analyzed by following thematic analysis.  The result found that a) the students’ high interest in recreational reading activity, and b) the reasons why they had high interest were caused by some advantages they agreed can develop their cognitive and affective aspects.